Цифрові моделі рельєфу на територію курорту Східниця - Кузик, З. (Видавництво Національного університету «Львівська політехніка», 2009)
В статье рассмотрены методы и способы цифрового моделирования рельэфа. Построены векторные и растровые цифровые модели рельэфа на горный карпатский регион курорта Схидныця в программах Surfer и ГИС Панорама.Сделано сравнительное описание ЦМР и практические рекомендации по их применению.Methods and ways of digital terrain modeling are considered in the article. Vektor and raster digital terrain models for the resort Skhidnycya in the moutain region of Carpathians are built in the programs Surfer and GIS Panorama. There is also done comparative analysis of DTM and practical recommendations concerning its application are given.